Fodor's essential Portugal - Bryson, Lucy (Travel writer); Humphreys, Liz (Journalist); Roberts, Alison; Taborda, Joana; Wallaya, Nora (Fodor's Travel, 2023)
Whether you want to explore Lisbon, go on a wine-tasting trip in the Douro Valley, or lounge on the beaches of the Algarve, the local Fodor's travel experts in Portugal are here to help! Fodor's Essential Portugal guidebook is packed with maps, carefully curated recommendations, and everything else you need to simplify your trip-planning process and make the most of your time.